PERSUASIVE COMMUNICATION STRATEGY OF THE “KEMBALIKAN BALIKU” STUDIO IN JAKARTA IN ATTRACTING YOUNG GENERATIONS TO PRESERVE THE PELIATAN BALINESE DANCE ART - Savitri, Gusti Devy; Tomohardjo, Irmulansati (Universitas Mercu Buana, 2025)
The Kembalikan Baliku Studio was established to preserve, maintain, and develop Balinese traditional arts, particularly the Peliatan style of Balinese dance, in this era of globalization for younger generations. However, young people often perceive traditional arts as rigid, outdated, and unfashionable. This perception has resulted in a lack of interest or even curiosity among many young individuals. By employing persuasive communication strategies, persuaders have been relatively successful in attracting the interest of the younger generation. This study aims to identify and analyze persuasive communication strategies used to attract young people to preserve the Peliatan Balinese dance art, and to examine the obstacles encountered in implementing these strategies. The research adopts a descriptive qualitative approach. Data collection methods include observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model. This study applies the persuasive communication strategy theory of Melvin L. DeFleur and Sandra J. Ball-Rokeach. The Kembalikan Baliku Studio identifies its target audience as the younger generation, as the nation’s successors, formulates engaging messages, determines methods by implementing several aspects—namely, canalizing, educational, informative, and persuasive approaches—and selects media channels to disseminate information through social media platforms such as Instagram and YouTube, as well as through public art performances. Additionally, various supporting and inhibiting factors influence the implementation of persuasive communication strategies in preserving traditional arts.